Athena Sings : Wagner and the Greeks - Lee, M. Owen, 1930-2019 (Book collections on Project MUSE., 2003)
Richard Wagner's knowledge of and passion for Greek drama was so profound that for Friedrich Nietzsche, Wagner was Aeschylus come alive again. Surprisingly little has been written about the pervasive influence of classical Greece on the quintessentially German master. In this elegant and masterfully argued book, renowned opera critic Father Owen Lee describes for the contemporary reader what it might have been like to witness a dramatic performance of Aeschylus in the theatre of Dionysus in Athens in the fifth century B.C. - something that Wagner himself undertook to do on several occasions, imagining a performance of The Oresteia in his mind, reading it aloud to his friends, providing his own commentary, and relating the Greek classic drama to his own romantic view. Father Lee also uses Wagner's writings on Greece and entries from his wife's diaries to cast new light on Tristan und Isolde, Die Meistersinger, Parsifal, and especially the mighty Ring cycle, where Wagner made extensive use of Greek elements to give structural unity and dramatic credibility to his Nordic and Germanic myths. No opera fan, argues Father Lee, can really understand Wagner saving Brünhilde without knowing the Athena who, in Greek drama, first brought justice to Athens. Written with a clarity and depth of knowledge that have characterized all Father Lee's books on the classics of Greece and Rome and made his six other volumes of opera bestsellers, Athena Sings traces the profound influence - an influence few music lovers are aware of - that Greek theatre and culture had on the most German of composers and his revolutionary musical dramas.